1995
DOI: 10.1002/jrs.1250261208
|View full text |Cite
|
Sign up to set email alerts
|

SERS of 1,8‐naphthyridine and the Raman spectra of two of its complexes

Abstract: The surface-enhanced Raman (SER) spectra of 1 $-naphthyridine (napy) adsorbed on silver colloids were measured. An edge-on configuration for the molecule is suggested, based on a comparison of the SER spectra of napy compared with the conventional Raman spectra of two of its complexes, Ag,(p-napy),(NO,), and OsO,(napy), the former serving as a model for an edge-on configuration of napy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has been reported that there is a close relationship between complexation and adsorption involving organic ligands at silver centers. 25,26,34 There are similarities between the SER spectrum of 2dtpy and the Raman spectrum of its Ag complex, [Ag(2dtpy)]NO 3 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…It has been reported that there is a close relationship between complexation and adsorption involving organic ligands at silver centers. 25,26,34 There are similarities between the SER spectrum of 2dtpy and the Raman spectrum of its Ag complex, [Ag(2dtpy)]NO 3 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 80%
“…In aromatic systems, similarities between the SER in silver colloids and the Raman spectrum of the Ag complex have been associated with a perpendicular position of the aromatic ring in the silver surface. 25,26,34 The similarities shown in the corresponding spectra of 2dtpy could be related to a perpendicular position of an aromatic ring in the silver surface, according to the adsorption mode of 2dtpy shown in Fig. 3b.…”
Section: Assigned To D(c--h)mentioning
confidence: 80%
See 2 more Smart Citations
“…Adsorption of N ‐bases on Ag + adsorption sites on Ag NP surface and the analogy between the surface complexes formed in this manner and the synthetically prepared Ag + complexes have been the subject of numerous studies . The presence of Ag(0) adsorption sites on Ag NPs modified by adsorbed chlorides at fractional surface coverage ≥0.6 (in borohydride‐reduced hydrosols) has been reported by Šloufová et al .…”
Section: Introductionmentioning
confidence: 92%